2021
DOI: 10.1111/add.15681
|View full text |Cite
|
Sign up to set email alerts
|

Are market mechanisms associated with alcohol and other drug treatment outcomes?

Abstract: Background and Aims The configuration of alcohol and other drug treatment service systems has been influenced by the uptake of market mechanisms for treatment funding and purchasing. This study measured the impact of market mechanisms for funding and purchasing alcohol and drug treatment services on client outcomes. Design An observational cross‐sectional study, employing multi‐level analysis: episodes of care data, nested within person‐level data, nested within treatment site and nested within organization. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Six studies were conducted in the United States, one of which included participants from the United States and Sweden [ 36 ], one study was conducted in the United Kingdom [ 37 ], one in South Africa [ 38 ] and one in Australia [ 39 ]. Eight studies were conducted in substance abuse treatment units or programs [ 37 , 38 , 40 , 41 , 42 , 43 , 44 ], while one study included AOD treatment centres but excluded centres focussed specifically on other drug use (i.e., those that did not include treatment for alcohol use) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies were conducted in the United States, one of which included participants from the United States and Sweden [ 36 ], one study was conducted in the United Kingdom [ 37 ], one in South Africa [ 38 ] and one in Australia [ 39 ]. Eight studies were conducted in substance abuse treatment units or programs [ 37 , 38 , 40 , 41 , 42 , 43 , 44 ], while one study included AOD treatment centres but excluded centres focussed specifically on other drug use (i.e., those that did not include treatment for alcohol use) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 summarises the methodological quality of included studies. Two studies scored ‘Yes’ on all Joanna Briggs criteria [ 39 , 41 ]. All studies scored ‘Yes’ across four out of eight criteria, including: ‘study subjects and setting described in detail’; ‘confounding factors identified’; ‘strategies to deal with confounding factors stated’; and ‘appropriate statistical analysis’.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations